Potential of Small-Scale Business Development and Sociocultural of Beef Cattle Farm at Pamekasan Regency: Case Study at Madura Island - Asri Nurul Huda; Aulia Puspita Anugera Yekti; Poespitasari Hazanah Ndaruc; Jaisy Aghniarahim Putritamara; Danung Nur Adli; Zulfaini Shamad (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2021)
Most of beef cattle farmers in Indonesia are dominated by small-scale farmer with ownership of three heads per household, homever the existence of small-scal farmer is expected to contribute to the development of the livestock sectore as whole. The interview was conducted with the total respondent at 30 beef cattle farmers at Larangan Dalam and Panaguan Village, Larangan Sub-District, Pamekasan Regency. The majority of the respondents' age range is 46-50 years old, with male breeders dominating, namely 76.67%, with the most educational qualifications being elementary school, namely 46.67%. The age and education level significantly affect the adoption rate of new technology. The objectives of raising livestock include fattening, breeding, and savings. In summary, the socio-culture was acted as important support in small-scale business development. The correlation between each socio-culture with new adaptation was a help to increase productivity in the future.Â